Monitoring the Impact of COVID-19 on Firms in Zambia : Results from Two Rounds of World Bank Enterprise Survey Follow-ups on COVID-19 - Finn, Arden; Ayana, Gemechu A.; Kanagavel, Rajee (World Bank, Washington, DC, 2021)
The Coronavirus disease 2019 (COVID-19) pandemic and its negative economic effects create a need for timely data and evidence to help monitor and mitigate the social and economic impacts of the crisis. To monitor the impacts of the COVID-19 pandemic and related containment measures on formal firms in Zambia and to inform the policy response, the World Bank is implementing several rounds of phone-based surveys of firms. The surveys in Zambia are follow-ons from the baseline enterprise survey that was conducted in Zambia immediately prior to the pandemic. These phone surveys allow for a better understanding of the effects of and responses to the COVID-19 pandemic on firm operations, hiring and firing, and expectations of future operations and labor demand in order to better tailor and implement interventions and policy responses and monitor their effects. This note summarizes the results of round 2 (R2) of the survey, conducted between December 19, 2020 and February 18, 2021. The information presented in this report is based on the sample of 570 firms that responded to both round 1 (R1) and round 2 (R2) surveys.